VALUES OF CARDIAL-ANKLE VASCULAR INDEX IN HEALTHY PEOPLE OF DIFFERENT AGE BY THE DATA OF ESSE-RF STUDY IN KEMEROVSKAYA REGION - A. N. Sumin; A. V. Shcheglova; N. V. Fedorova; G. V. Artamonova (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To study the values of cardial-ankle vascular index (CAVI) in healthy persons of various age by the data of multicenter epidemiological study "Epidemiology of cardiovascular diseases and risk factors in Russian Federation" (ESSE-RF) in Kemerovskaya Region (KR). Material and methods. The study was conducted on random population selection of adult males and females, age 25-64 y.o. Study was performed in March-October 2013. Final selection consisted of 1610 persons. In 1595 we did the measurement of peripheral arteries rigidity with CAVI by the device VaSeraVS-1000 (Fukuda Denshi, Japan). For the measurement of normal CAVI we collected a group of healthy volunteers — 190 (11,7%) persons.Results. Among the whole cohort, CAVI was in reference range: 7,1 (6,4; 8,0). In healthy persons CAVI was lower — 6,7 (6,1; 7,4), than in general population. In analysis of CAVI within different age groups among healthy persons, CAVI was much higher in men than in women. Though different age groups CAVI increased from 6,2 at the age 21-30 y.o. to 7,8 by 61-70 y.o., grade of increase was 25,8%. In older age group, there was more rapid increase of stiffness index. The highest correlation of CAVI among participants was with the age (r=0,402; р<0,001), and with the values of systolic and diastolic arterial pressure (BP) — r=0,348; r=0,368; resp., (р<0,001), smoking duration — r=0,494 (р<0,001) and blood creatinine level — r=0,198 (p=0,006).Conclusion. The values of CAVI in healthy persons by the data from population study ESSE-RF in KR were 6,2 to 7,8 in various age groups. There was linear increase of CAVI every 10 years by 28%. Except the age, CAVI correlated with BP, smoking duration, cholesterol and creatinine levels. The results of this study can be included into CAVI evaluations in screenings, and for formulation of normal values for Russian population.